An assessment of CCS costs, barriers and potential. (November 2018) - Budinis, Sara; Krevor, Samuel; Dowell, Niall Mac; Brandon, Nigel; Hawkes, Adam
Abstract: Global decarbonisation scenarios include Carbon Capture and Storage (CCS) as a key technology to reduce carbon dioxide (CO2 ) emissions from the power and industrial sectors. However, few large scale CCS plants are operating worldwide. This mismatch between expectations and reality is caused by a series of barriers which are preventing this technology from being adopted more widely. The goal of this paper is to identify and review the barriers to CCS development, with a focus on recent cost estimates, and to assess the potential of CCS to enable access to fossil fuels without causing dangerous levels of climate change. The result of the review shows that no CCS barriers are exclusively technical, with CCS cost being the most significant hurdle in the short to medium term. In the long term, CCS is found to be very cost effective when compared with other mitigation options. Cost estimates exhibit a high range, which depends on process type, separation technology, CO2 transport technique and storage site. CCS potential has been quantified by comparing the amount of fossil fuels that could be used globally with and without CCS. In modelled energy system transition pathways that limit global warming to less than 2 °C, scenarios without CCS result in 26% of fossil fuel reserves being consumed by 2050, against 37% being consumed when CCS is available. However, by 2100, the scenarios without CCS have only consumed slightly more fossil fuel reserves (33%), whereas scenarios with CCS available end up consuming 65% of reserves. It was also shown that the residual emissions from CCS facilities is the key factor limiting long term uptake, rather than cost. Overall, the results show that worldwide CCS adoption will be critical if fossil fuel reserves are to continue to be substantively accessed whilst still meeting climate targets. Highlights: This paper reviews barriers to global CCS adoption and also considers its potential impact on 'unburnable' reserves. CCS availability has a large bearing on the extent of fossil fuel consumption in climate-constrained scenarios. In the medium term (up to 2050) scenarios including CCS result in 37% of fossil fuel reserves being consumed. In the long term (up to 2100) scenarios with CCS available end up consuming 65% of reserves. Residual emissions from CCS facilities are a key factor limiting long term uptake.